Field‐programmable gate array‐based laboratory oriented to control theory courses - Cruz‐Miguel, Edson E.; Rodríguez‐Reséndiz, Juvenal; García‐Martínez, José R.; Camarillo‐Gómez, Karla A.; Pérez‐Soto, Gerardo I. (Computer applications in engineering education, 2019)
This article presents a methodology to improve the performance of learning of students in the major of Automation Engineering, through the development of a multidisciplinary project that involves the use of contemporary technological tools and knowledge of previous subjects. It is sought to add in their educational training, theory and practice for the student, learning, new knowledge, and skills within their training as an engineer. Despite advances in teaching methods and the inclusion of contemporary tools in the learning process, the success rate is low. A qualitative and quantitative analysis of student learning is made by integrating a multidisciplinary project based on contemporary tools compared with other reviewed works. This laboratory based on a field‐programmable gate array helps the student to acquire skills related to the implementation of reconfigurable logic and instrumentation applied to control theory. The development of the final project involves the design of a graphic user interface, hardware description, communication protocols, and implementation of motion control, it is looking for is that the student can relate theory to practice in order to motivate and increase skills and knowledge, as well as solving both didactic and industrial problems. The results obtained show that the students are satisfied with the course and that the experience with the integration of this type of multidisciplinary projects directly impacts the motivation and learning of the student, considerably increased developed based on the specific indicators that the Querétaro State University has accredited by Accreditation Board for Engineering and Technology since 2016.